2010
DOI: 10.1002/pmic.201000209
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of earthworm Eisenia fetida proteomes during cadmium exposure: An ecotoxicoproteomics approach

Abstract: Identification of differential proteomic responses to cadmium (Cd) would provide a means for better understanding the survival mechanisms of the earthworm, Eisenia fetida, living in a Cd-polluted environment, and the stress responses can be assessed by ecotoxiptoromics approaches. Extracts of whole earthworm collected at days 7, 14, 21, and 28 after Cd exposure were analyzed by 2-DE and quantitative image analysis. In total, 143 proteins demonstrated significant regulation in at least at one time point, and 56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 68 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…Some recent studies have shown that both NMR-based metabolomics and 2-DE-based proteomics on earthworm Eisenia fetida have great potential to elucidate the toxicological effects and mechanisms induced by environmental contaminants, such as heavy metals (e.g., cadmium) and organic chemicals (e.g., phenanthrene) [29,30]. To our knowledge, however, no combined proteomic and metabolomic investigation has been carried out in ecotoxicology using E. fetida as a bioindicator.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…Some recent studies have shown that both NMR-based metabolomics and 2-DE-based proteomics on earthworm Eisenia fetida have great potential to elucidate the toxicological effects and mechanisms induced by environmental contaminants, such as heavy metals (e.g., cadmium) and organic chemicals (e.g., phenanthrene) [29,30]. To our knowledge, however, no combined proteomic and metabolomic investigation has been carried out in ecotoxicology using E. fetida as a bioindicator.…”
Section: Introductionmentioning
confidence: 98%
“…mean the disturbance in innate immunity, which was also found in Cd-exposed E. fetida [30]. Heat shock proteins are ubiquitous molecular chaperones that are involved in the inhibition of cell apoptosis caused by stressors.…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…There are only few proteomic studies and none with NMs. These proteomic investigations include studies with the earthworm Eisenia fetida exposed to brominated flame‐retardants, phenanthrene and Cd, and studies with the springtail Paronychiurus kimi exposed to Cd …”
Section: Introductionmentioning
confidence: 99%